2020
DOI: 10.1038/s41467-020-16947-6
|View full text |Cite
|
Sign up to set email alerts
|

Nolz1 expression is required in dopaminergic axon guidance and striatal innervation

Abstract: Midbrain dopaminergic (DA) axons make long longitudinal projections towards the striatum. Despite the importance of DA striatal innervation, processes involved in establishment of DA axonal connectivity remain largely unknown. Here we demonstrate a striatal-specific requirement of transcriptional regulator Nolz1 in establishing DA circuitry formation. DA projections are misguided and fail to innervate the striatum in both constitutive and striatal-specific Nolz1 mutant embryos. The lack of striatal Nolz1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…We utilized a similar approach to extract SVZ/MZ cells from the GEs that had high expression levels of Dcx, which displayed fairly clean segregation between LGE, MGE and CGE resulting in 11 cell clusters (total of 12,307 high Dcx-expressing cells with 3,900 from LGE, 3,902 from MGE and 4,505 from CGE; Figure 6-figure supplement 1A). We observed clusters containing previously described region-enriched genes such Nkx2.1, Lhx6 and Lhx8 in the MGE, and Nr2f1 and Nr2f2 for CGE (Kanatani et al, 2008;Lodato et al, 2011); the expression profile of these genes was confirmed with in situ hybridizations (Figure 6A (Soleilhavoup et al, 2020;Zhang et al, 2019), and Aldh1a3/Raldh3 is critical for generation of LGE-derived neurons (Chatzi et al, 2011). Ebf1, a marker for direct pathway striatal neurons (Lobo et al, 2008), is also expressed in this region but not as tightly restricted to this narrow domain as the other genes (Figure 6D).…”
Section: Transcriptional Heterogeneity In Svz/mz Cells Within the Ven...supporting
confidence: 76%
See 1 more Smart Citation
“…We utilized a similar approach to extract SVZ/MZ cells from the GEs that had high expression levels of Dcx, which displayed fairly clean segregation between LGE, MGE and CGE resulting in 11 cell clusters (total of 12,307 high Dcx-expressing cells with 3,900 from LGE, 3,902 from MGE and 4,505 from CGE; Figure 6-figure supplement 1A). We observed clusters containing previously described region-enriched genes such Nkx2.1, Lhx6 and Lhx8 in the MGE, and Nr2f1 and Nr2f2 for CGE (Kanatani et al, 2008;Lodato et al, 2011); the expression profile of these genes was confirmed with in situ hybridizations (Figure 6A (Soleilhavoup et al, 2020;Zhang et al, 2019), and Aldh1a3/Raldh3 is critical for generation of LGE-derived neurons (Chatzi et al, 2011). Ebf1, a marker for direct pathway striatal neurons (Lobo et al, 2008), is also expressed in this region but not as tightly restricted to this narrow domain as the other genes (Figure 6D).…”
Section: Transcriptional Heterogeneity In Svz/mz Cells Within the Ven...supporting
confidence: 76%
“…For example, Mbip and Rprm show a complimentary expression profile at the VZ/SVZ and SVZ/MZ border in MGE, respectively. We observed several genes (Mpped2, Pcsk1n, Aldh1a3, Zfhx3 and Zfp503) strongly enriched at the SVZ/MZ boundary in the ventral LGE (Figure 6 and Figure 6-figure supplement 2), which likely represent future medium spiny neurons of the striatum (Chatzi et al, 2011;Soleilhavoup et al, 2020;Zhang et al, 2019). Within the CGE, Nrp2, Rprm and Zfp503 are enriched in the ventral region whereas Mpped2, Ccnd2 and Flrt2 are enriched in the SVZ/MZ of the dorsal CGE.…”
Section: Discussionmentioning
confidence: 83%
“…Although the precise cause of Zfp503 -/- neonatal lethality is unclear, expression of Zfp503 in the developing spinal cord and its role in motor neuron development could explain the atelectasis we noted in the lungs 12 . More recently, Soleilhavoup and colleagues have demonstrated that Zfp503 is required for proper innervation of the striatum by midbrain dopaminergic neurons in mouse and its deletion results in a nigral to pallidal lineage conversion and changes in secreted factors in the striatum 54 ; thus, we hypothesize that a developmental brain defect could contribute to perinatal lethality.…”
Section: Discussionmentioning
confidence: 81%
“…Axon guiding molecules are expressed in the nigro-striatal projection system, whereas ephrins are mainly expressed in the striatum [17,27]. Inactivation of the FTO gene impairs DA receptors, controls activity and behavior of neurons in a dose-dependent manner.…”
Section: Identi Cation Of Key Target Genes For Fto Functionmentioning
confidence: 99%
“…Studies report that axon guidance regulation of dopaminergic neurons and spinal motoneurons plays important role in brain development [14,15]. The divergent member of the erythropoietin-producing hepatocyte receptor-interacting proteins (ephrins) mediate cell-cell communication thus regulating axon guidance and neural projection.…”
Section: Introductionmentioning
confidence: 99%